2010
DOI: 10.1017/s1074070800003862
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Import Demand for Wooden Beds in the U.S.

Abstract: The market of wooden beds in the U.S. has been flooded with imports from China and Vietnam in recent years. Static and dynamic Almost Ideal Demand System models are used to assess the import demand for wooden beds from the top seven supplying countries. The analyses reveal that the antidumping investigation on China has some temporary trade depression effect on China, but trade diversion occurs to Vietnam, Indonesia, Canada, and Brazil. The formal implementation of antidumping duties since 2005 has not shown a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
0
18
0
6
Order By: Relevance
“…The political climate in Vietnam has been relatively stable in recent years and its workforce is generally diligent. Vietnam also has benefited from the US antidumping investigation that resulted in duties being placed on Chinese wooden bedroom furniture since 2005 (Wan et al, 2010a). Survey studies revealed that a large number of Taiwanese furniture firms have moved their factories to Vietnam in recent years (Tung, 2009).…”
Section: Vietnam's Growthmentioning
confidence: 99%
“…The political climate in Vietnam has been relatively stable in recent years and its workforce is generally diligent. Vietnam also has benefited from the US antidumping investigation that resulted in duties being placed on Chinese wooden bedroom furniture since 2005 (Wan et al, 2010a). Survey studies revealed that a large number of Taiwanese furniture firms have moved their factories to Vietnam in recent years (Tung, 2009).…”
Section: Vietnam's Growthmentioning
confidence: 99%
“…If more than one non-stationary time series is found to be co-integrated, the ECM-AIDS model can be introduced to estimate the short-term dynamics in which a dependent variable deviates and returns to long-term equilibrium after a change in an independent variable. At the same time, it reveals the longterm equilibrium and co-integration relationship among variables in equation (1) while the residuals that are calculated from the static AIDS are stationary (Wan et al 2010, Nzaku et al 2012, Wang 2013.…”
Section: Methodsmentioning
confidence: 96%
“…We estimate import demand elasticities for each grain commodity by source countries using a source differentiated Almost Ideal Demand System model, a model that has been frequently used in the literature to analyze the import demand (Carew, Florkowski, & He, 2004;Henneberry & Hwang, 2007;Wan, Sun, & Grebner, 2010;Yang & Koo, 1994). The model specification is: 5…”
Section: The Import Demand Modelmentioning
confidence: 99%